Impelentasi Kebijakan Rencana Umum Tata Ruang Kota - Winarti ' (Universitas Riau, 2011)
This research aim at the efectiveness RUTRK – RDTRK 1992 – 2012 Colomadu Region inKaranganyar Residence. Will be implemented and to seen from it’s content and contexs policy, alsothe constrains and push factor in implementation the policy it is the research of target. How theregulation of agricultural land use?. Colomadu located in a very strategic and high economic poten-tial, mayority its lands are agricultural land use, transfer from agriculture to business oriented it’svery high. This research includes qualitative research with informants bureaucracy, developer,businessman and farmer land owners. which is determined by swowbolling technique. The collecteddata were analyzed with the method of interactive analysis. The result of the research indicated that: the implementation RUTRK – RDTRK 1992 – 2012 Colomadu Region is more economic prioritythan law enforcement for existence agricultural land use as “food stock” and land use control, thisphenomenon will be sustainable for the strategy to protec agriculture with agricultural land asenternity land.